A Cost Based Approach to Project Management : planning and controlling construction project costs - Hanioglu, Mehmet Nihat (New York: Routledge, 2023)
"A Cost Based Approach to Project Management: Planning and Controlling Construction Project Costs introduces early-career architects, construction managers, civil engineers, and facility managers to the essentials of delivering projects on-time and at cost. Drawing on the author's decades of experience managing marquee building and infrastructure projects around the world, this primer offers busy professionals a crash course in budgeting, cost estimating, scheduling, and cost control. Chapters break down the details of cost elements, structuring project costs, and integrating budget with schedule, providing novice project managers with the key skills to plan and execute construction projects with confidence and precision. Features: Illustrates the principles of project management and the essentials of cost planning and control with easy-to-understand examples from the construction industry Includes step-by-step details of project planning, cost-estimating, and management processes Offers clear, cost-based methods for defining scope, preparing bids, and planning for contingencies, as well monitoring progress and determining when to take remedial action Contains a user-friendly guide to project management acronyms and terminology Provides sample construction schedules, budgets, and progress report forms An ideal resource for self-study, on-the-job training, or courses in construction, architecture, or civil engineering project management, A Cost Based Approach to Project Management makes a worthy addition to the aspiring project manager's reference shelf"--
Includes bibliographical references and index.
Keywords: Building -- Cost control; Construction industry -- Costs; Construction industry -- Cost control; Building superintendence; Project management